Potencial agronômico e seleção de genótipos de feijoeiro comum para obtenção de genitores potenciais: sistemas orgânico vs. convencional - Carreño Siqueira, José Andrés (2023)
Organic agriculture is one of the most used terms to designate non-conventional models of agriculture, which adopt basic principles of management of natural resources, soil, plant nutrition and seed production. One of the biggest obstacles to organic production is the scarcity of seeds from organic systems, which means that producers have to obtain them from a conventional source. The main objective of this work is the evaluation of different bean genotypes present in the seed repository of the Federal University of Uberlândia (UFU), in the organic and conventional planting systems. Selecting adapted genotypes to start the improvement program with adaptation to the organic system, thus reducing the dependence of producers on pesticides. The experimental design used was a 2 x 7 factorial in randomized blocks experimental design, with four replications: The first factors were the production systems (conventional and organic) and according to the 7 genotypes (UFU-1; UFU-2; UFU3; UFU-4; UFU-5; UFU-6 UFU-7), UFU-1 being a hybrid obtained between the UFU-4 and UFU-7 genotypes; UFU-2 and UFU-3 were commercial genotypes; and UFU-4, UFU-5, UFU6 and UFU-7 genotypes from the UFU Monte Carmelo germplasm bank. Evaluations were carried out for the agronomic characters of the plants, namely: height, number of branches, length and volume of roots, dry matter, SPAD, chlorophyll, leaf area index, number of flowers, number of pods, number of seeds per pod, mass of 100 seeds and productivity of genotypes. The results showed a distinct behavior of the genotypes for each production system. The recommended genotypes for the organic system were UFU-2, UFU-6 and UFU-7 with higher productivity. For the conventional system, the genotype with the highest adaptation was for UFU-4 with the highest productive yield. As a final conclusion, it is necessary to select common bean genotypes adapted for the organic system.